224k views
5 votes
Solve the following equation by the quadratic formula. x 2 + x - 1 = 0

2 Answers

5 votes

Answer

x is 1.62 or -0.62

Explanation:

User Niels De Bruin
by
5.1k points
4 votes

Quadratic Formula:


\boxed{ \bf{x = (-b \pm √(b^2 - 4ac))/(2a)}}

Given Quadratic Equation:

x² + x - 1 = 0

a = 1 (Quadratic coefficient)

b = 1 (Linear coefficient)

c = -1 (Constant coefficient)

By substituting values in the formula, we get:


\rm \longrightarrow x = (-1 \pm √(1^2 - 4(1)( - 1)))/(2 * 1) \\ \\ \rm \longrightarrow x = ( - 1 \pm √(1 + 4) )/(2) \\ \\ \rm \longrightarrow x = ( - 1 \pm √(5) )/(2)

User Bergrebell
by
5.5k points